2017
DOI: 10.1371/journal.pone.0173816
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activities during walking and running at energetically optimal transition speed under normobaric hypoxia on gradient slopes

Abstract: Energy cost of transport per unit distance (CoT; J·kg-1·km-1) displays a U-shaped fashion in walking and a linear fashion in running as a function of gait speed (v; km·h-1). There exists an intersection between U-shaped and linear CoT-v relationships, being termed energetically optimal transition speed (EOTS; km·h-1). Combined effects of gradient and moderate normobaric hypoxia (15.0% O2) were investigated when walking and running at the EOTS in fifteen young males. The CoT values were determined at eight walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 61 publications
5
16
0
Order By: Relevance
“…These results were equivalent to those of our recent studies that measured TA activity during walking and running at the EOTS (Abe, Fukuoka & Horiuchi, 2017;Abe et al, 2018), which suggested that the motor unit recruitment pattern of the TA shifted more toward Type I (slow twitch) fibers rather than Type II (fast twitch) fibers after the walk-run transition. Several studies have also reported that an abrupt increase in TA activity associated with the walk-run transition (Hreljac, 1995;Hreljac et al, 2008;Bartlett & Kram, 2008;Malcolm et al, 2009;Shih et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results were equivalent to those of our recent studies that measured TA activity during walking and running at the EOTS (Abe, Fukuoka & Horiuchi, 2017;Abe et al, 2018), which suggested that the motor unit recruitment pattern of the TA shifted more toward Type I (slow twitch) fibers rather than Type II (fast twitch) fibers after the walk-run transition. Several studies have also reported that an abrupt increase in TA activity associated with the walk-run transition (Hreljac, 1995;Hreljac et al, 2008;Bartlett & Kram, 2008;Malcolm et al, 2009;Shih et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…An abrupt increase in muscle activity of the dorsiflexor (tibialis anterior; TA) has been observed when participants walked at a speed close to the PTS (Hreljac, 1995;Hreljac et al, 2008;Prilutsky & Gregor, 2001; Bartlett & Kram, 2008;Malcolm et al, 2009;Shih et al, 2016), and our recent studies showed muscle activity of the TA decreased when participants switched from walking to running at the EOTS (Abe, Fukuoka & Horiuchi, 2017;Abe et al, 2018). In association with a decrease in TA activity when switching the gait pattern, mean power frequency (MPF; Hz) of the TA became lower, suggesting that more Type 1 muscle fibers were recruited in the TA during running than walking at the EOTS.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, hyperoxia depresses peripheral chemoreceptor, resulting in a decrease in ventilatory response [ 16 , 17 ]. As far as we know, the ES and/or EOTS have not been measured under different O 2 conditions except for our recent hypoxic studies [ 10 , 18 ]. Saving the whole-body energy expenditure at a given gait speed can provide an effective use of endurance capacity, that is, a possible combination of the rightward (faster) and downward (lesser metabolic) shifts of the U-shaped and linear CoT- v relationships will occur under hyperoxia relative to normoxia (Additional file 1 : Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…An abrupt increase in muscle activity of the dorsiflexor (tibialis anterior; TA) has been 54 observed when participants walked at a speed close to the PTS (56 2016), and our recent studies showed muscle activity of the TA decreased when participants 57 switched from walking to running at the EOTS (Abe, Fukuoka & Horiuchi, 2017; Abe et al, 58 2018). In association with a decrease in TA activity when switching the gait pattern, mean power 59 frequency (MPF; Hz) of the TA became lower, suggesting that more Type 1 muscle fibers were 60 recruited in the TA during running than walking at the EOTS.…”
mentioning
confidence: 88%